Efeito da led terapia no comportamento do consumo de oxigênio durante testes de corrida com carga incremental e retangular - Mezzaroba, Paulo Victor (2015)
Phototherapy is a widely used resource in the health field, with responses related to tissue regeneration, anagelsic and anti-inflammatory effects; however, only recently has drawn attention for the associated use with physical exercise resulting physiological and metabolic modification during and after different types of effort. Despite extensive descriptions of the effects of phototherapy in aerobic metabolismo componentes, such as: mitochondrial structure and function, enzymatic activity, metabolites removal and microcirculation, there is no great theoretical basis on the responses of phototerapy in aerobic exercise in humans. One way to describe and explain the possible biological mechanisms of phototherapy on this metabolismo is through the analyisis of respiratory parameters that may indicate central and peripheral changes caused by physical exercise without requiring invasive evaluations. Thus, the aim of this study was to investigate the effect of LED therapy in the oxygen uptake behavior during incremental and square-wave intensity running tests. Twenty-six healthy and physically active men were evaluated (27.8 ± 1.7 years, 78.6 ± 9.1 kg, 178,1 ± 5,9 cm e 17,5 ± 4,0 % fat). Participants performed five visits in the laboratory to: anthropometric evaluation and familiarization to the test and the ergometer (treadmill) (1st visit), execution of two maximal tests of incremental load in placebo (PLA) and LED therapy (LED) conditions (2nd and 3rd visists), and two square-waves load tests in PLA and LED conditions (4th and 5th visits). The experimental conditions were performed in random order, with double blind control and minimum interval between tests of 48 hours over a maximum period of three weeks. The infrared LED was applied in two regions of the quadríceps muscle, two regions of the biceps femoris and one region of the gastrocnemius, with wavelength diodes of 850 nm, and energy density of 3.7 J·cm-2. The incremental load test was conducted with initial speed at 8 km·h-1, increments of 1 km·h-1 every three minutes with a constant gradient of 1%, with control of: heart rate (HR) for the maximum and submaximum HR (HRmax and HRsub) determination, gas exchange to determine ventilatory threshold (VT), maximum and submaximum oxygen uptake (VO2max and VO2sub), rating of perceived exertion (RPE) and the blood lactate behavior before and after test. The intensity of the square-wave load test on the heavy effort domain was determined from the VT and VO2max values obtained in the incremental load test, the subjects had the HR, RPE and VO2 evaluated during the six-minute test, which was used for the determination of VO2 kinetics parameters. The data were presented as mean ± standard deviation with the normality checked by the Shapiro-Wilk test, the paired Student t test and the Wilcoxon test were used to compare the PLA and LED conditions, using sifnificance level of P < 0.05. The main results showed significant effect of LED therapy on VO2max (PLA = 47.2 ± 5.7 e LED = 48.0 ± 5.4 ml·kg·min-1), VO2 related to VT (PLA = 40.1 ± 4.6 e LED = 41.3 ± 4.3 ml·kg·min-1), HRmax (PLA = 195 ± 3.4 e LED = 193 ± 3.9 b·min-1), the removal of blood lactate and VO2sub, HRsub, and RPE of the intermediate stages of the incremental load test and square-wave load test. In addtiom, LED condition reduced the amplitude (PLA = 311.8 ± 120.8 e LED = 262.4 ± 99.3 ml·min-1) and relative contribution (PLA = 11.8 ± 4.1 e LED = 9.9 ± 3.5 %) of the slow component of VO2 kinetic. With the obtained results, it is concluded that the use o LED therapy modifies the VO2 behavior and significantly change HRmax and HRsub, psychophysiological parameters, and the metabolites removal, directly affecting the running performance in incremental and square-wave load testing. We suggest the uso of LED therapy prior to exercise in healthy and physically active subjects as a pre-activation strategy for the oxidative metabolism and target muscle.